A Catalogue of Ancient Egyptian Sundials. (November 2016) - Symons, Sarah; Khurana, Himanshi
Ancient Egypt furnishes us with examples of different types of sundial from the New Kingdom ( c. 1500b.c. ) onward. Some objects that have been described as sundials are better evidenced as time-keeping devices than others. Hypotheses about the development and even the method of using sundials remain controversial in a few cases. New finds also add to our understanding of the development of sundials in Egypt. Here, we describe an attempt to catalogue ancient Egyptian sundials and the results that are emerging from the investigation.